Análise de flavonóides por cromatografia líquida de alta eficiência (CLAE), com ensaios in vitro do potencial antioxidante em folhas de Smilax fluminensis Steud. (Smilacacea) - Petrica, Edith Eunice Arthur (2012)
The objective of this study was to identify and quantify flavonoids present in the ethanol extract of leaves of Smilax fluminensis by high performance liquid chromatography (HPLC-UV), to evaluate the antioxidant potential of the fractions, isolate and identify some flavonoids. Were identified and quantified by HPLC, eight flavonoids: agatisflavone, amentoflavone, apigenin, kaempferol, quercetin, quercitrin, rutin and taxifolin. The content of flavonoids identified by HPLC ranged from 2.0 ppm to 125 ppm. The antioxidant potential was shown by the fractions above 90% of DPPH sequestration in most fractions with EC50 4.0 mg/mL to 14.0 mg/mL. Have been isolated and identified flavonoids: Quercetin[3-O- -L-ramnopyranosyl(1’’’ 6’’)- -D-glucopyranosyl]-7-O- - L-ramnopyranoside (SG116-124); quercetin-3-O-b-D-galactopyranoside (hiperin) (SG125-161); Quercetin-3-O- -L-ramnopyranosyl(1’’’ 6’’)-O- - D-glucopyranoside, (SG201-215) and quercetin (SH29-32). The HPLC method allowed the identification and quantification of flavonoids, supported by analysis of Nuclear Magnetic Resonance - NMR 1H and 13C and mass spectrometry.